The use of multiple regression analysis to study the relationship between the amplitudes of EEG rhythms within one derivation with mental retardation - B. Lobasyuk; L. Bartsevich; A. Zamkovaya (Kazimierz Wielki University, 2023)
Using the calculation of coefficients of multiple linear regression and two-dimensional correlation, we studied the mutual influence (functional connectivity) between the amplitudes of EEG rhythms within one lead in mentally retarded persons. Multiple regression equations were geometrically interpreted using polycyclic multigraphs. As a result of the studies and calculations, it was revealed that with mental retardation, the number of regression coefficients is determined more than in the norm. In the control group of sinistrals, more regression coefficients were detected between the amplitudes of EEG rhythms within one lead than in dextrals. Apparently, the results obtained reflect the features of the network semantic-topological brain. A greater number of regression coefficients within the full lead in dextrals, under normal conditions, was expressed in the sinister hemisphere, and sinistrals in the dextral one. In mentally retarded persons, on the contrary, during the reign, a greater number of regression coefficients appeared in the dextral hemisphere, and in sinistrals (although not significantly) in the sinistral. It can also be assumed that the connections-relationships found in the leads reflect projections in these leads of the EEG rhythm generators. The foregoing makes it possible to consider the regression connections-relations calculated in the analysis of the relationship between the amplitudes of EEG rhythms as units of neurophysiological activity.